Pengembangan Sistem Informasi Monitoring Peternakan Ayam berbasis Mobile menggunakan React Native dan Restfull Web Service (Studi Kasus: Peternakan Alfa Sentosa) - Muhammad Fikri Fadlurrahman; Issa Arwani; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Alfa Setosa Farm is one of the chicken farming industries located in Bendosari Village, Kademangan District, Blitar Regency. Alfa Sentosa has been established since 2018 and focuses on producing chicken meat. Alfa Sentosa Farm has a total capacity of 7,000 (seven thousand) chickens for each production. The production period carried out by Alfa Sentosa is usually takes about 30 (thirty) to 40 (forty) days to produce chicken meat. Alfa Sentosa itself also partners with PT. Charoen Pokphand Indonesia for the supply of chicken seeds, feed, and vitamins. However, there is a problem with data recording which is still done manually using handwriting on an existing form. After writing the form, the employee takes a picture of the form and then reports it to the Alfa Sentosa farm owner via the online chat application. The report is divided into 3, namely the DOC (Day Old Chicken) report when it arrives, the daily report for feed and medicinal use, and the report when it is harvested. In addition, these reports are not well documented because they only use photos and are not neatly stored, making it a little difficult to analyze the percentage graphs of Alfa Sentosa farms. So from these problems, the development of an Information System for the archiving and recording of reports was carried out to help maximize business processes. System development begins with requirements analysis by interviewing Alfa Sentosa farm's owner. Based on the results of requirements analysis, it is continued with the design in the form of Sequence Diagrams, Class Diagrams, Physical Data Models, API design, and User Interface design. The system implementation is carried out in the form of mobile apps with the Laravel and React native framework. These two technologies will communicate using RESTFUL Web Service. For the testing, the blackbox testing is used, which gets all valid values and usability testing which gets average value 86 that means the system is well received.